Development of a Highly Sensitive Neurofilament Light Chain Assay on an Automated Immunoassay Platform - Lee, Stephen; Plavina, Tatiana; Singh, Carol M.; Xiong, Kuangnan; Qiu, Xiaolei; Rudick, Richard A.; Calabresi, Peter A.; Stevenson, Lauren; Graham, Danielle; Raitcheva, Denitza; Green, Christopher; Matias, Madeleine; et al. (Frontiers in Neurology, 2022)
Background: Neurofilament light chain (NfL) is an axonal cytoskeletal protein that is released into the extracellular space following neuronal or axonal injury associated with neurological conditions such as multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), and other diseases. NfL is detectable in cerebrospinal fluid (CSF) and blood. Numerous studies in MS have demonstrated that NfL correlates with disease activity, predicts disease progression, and is reduced by treatment with MS disease-modifying drugs, making NfL an attractive candidate to supplement existing clinical and imaging measures in MS. However, for NfL to achieve its potential as a clinically useful biomarker for clinical decision-making or drug development, a standardized, practical, widely accessible assay is needed. Our objective was to validate the analytical performance of the novel serum neurofilament light (sNfl) assay on the ADVIA Centaur® XP immunoassay system. Methods: The research assay was evaluated on the ADVIA Centaur XP immunoassay system from Siemens Healthineers. The lower limit of quantitation (LLoQ), intra-assay variation, assay range, cross-reactivity with neurofilament medium and heavy chains, and effect of interfering substances were determined. NfL assay values in serum and CSF were compared with radiological and clinical disease activity measures in patients with MS and ALS, respectively. This assay was further optimized to utilize serum, plasma, and CSF sample types and transferred to Siemens’ CLIA laboratory, where it was analytically validated as a laboratory-developed test. Results: In this study, a LLoQ of 1.85 pg/mL, intra-assay variation of <6%, and an assay range of up to 646 pg/mL were demonstrated. A cross-reactivity of <0.7% with neurofilament medium and heavy chains was observed, and the assay was not significantly affected by various interfering substances encountered in clinical specimens. Serum and CSF NfL assay values were associated with radiological and clinical disease activity measures in patients with MS and ALS, respectively. Conclusion: The analytical performance of the NfL assay fulfilled all acceptance criteria; therefore, we believe the assay is acceptable for use in both research and clinical practice settings to determine elevated sNfL levels in patients.